Pengaruh Penggunaan Media Manipulatif terhadap Hasil Belajar Matematika Siswa Kelas V SDN 52 Kota Bengkulu - Kurniawati, Ike; Karjiyati, Victoria; Dalifa, Dalifa (Jurnal PGSD, 2019)
This study aims to determine the effect of manipulative media on student learning outcomes in learning mathematics class V SDN 52 Kota Bengkulu. This research is a quantitative type. The research method used is Quasi Experimental with design type The Matching Only Pretest-Posttest Control Group Design. The population in this study is all students of grade V SDN Kota Bengkulu using KTSP. While the sample of class V students in SDN 52 Kota Bengkulu consists of VA, VB, VC and VD. The sampling technique uses cluster random sampling. From the scramble obtained VC class of 28 students as experiment class and VA class amounted to 29 students as control class. The research instrument used in the form of cognitive learning result test is in the form of multiple choice questions given through pretest and posttest in the experimental class and control class. Data of this research are analyzed by using descriptive analysis and inferential analysis that is t-test. Data of research result which is processed by using t-test is got tcount value 2,84 and t table value equal to 1,625. Systematically seen t count (2.84)> t table (1,625) at 5% significant level, it can be concluded that there is influence of the use of manipulative media on student learning outcomes on learning matemtika class V SDN 52 Kota Bengkulu.